The use of placebos in controlled trials of surgical interventions: a brief history - Wartolowska, K; Beard, D; Carr, A (SAGE Publications, 2018)
Inferences about the effects of treatments, including surgical treatments, rely on making comparisons. These comparisons may be with patient’s symptoms before a treatment has been applied. For example, the return of hearing after puncturing the ear drum (tympanotomy) in certain kinds of longstanding deafness can be so dramatic that the change can be confidently ascribed to the treatment.1,2 More usually, treatments have more modest effects, and alternative treatments may differ from each other only slightly, if at all. In these circumstances, disagreements are common about the mechanisms, the magnitude of any effects and the value of a particular treatment. Examples include disputes about different ways of treating wounds,3,4 the timing and methods of limb amputations,5–10 and about lithotripsy as an alternative to lithotomy.11–13